2015
DOI: 10.1002/stem.1843
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase and Wnt Signaling Regulate Human Ductal Carcinoma In Situ Stem Cell Activity and Response to Radiotherapy

Abstract: Cancer stem cells (CSCs) can avoid or efficiently repair DNA damage from radio and chemotherapy, which suggests they play a role in disease recurrence. Twenty percentage of patients treated with surgery and radiotherapy for ductal carcinoma in situ (DCIS) of the breast recur and our previous data show that high grade DCIS have increased numbers of CSCs. Here, we investigate the role of focal adhesion kinase (FAK) and Wnt pathways in DCIS stem cells and their capacity to survive irradiation. Using DCIS cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 55 publications
1
56
0
Order By: Relevance
“…In particular, it has been suggested that a small subpopulation of cells within tumors, called cancer stem cells (CSCs), by virtue of their relative resistance to chemotherapy may contribute to tumor recurrence (5,6). Consistent with these reports, several groups reported enrichment for CSCs when solid cancers were subjected to classical anticancer treatment (7)(8)(9)(10)(11). In accumulation, these studies suggest that significant improvement in patient outcome will require drugs that selectively target CSCs in combination with conventional chemotherapeutic regimens that target rapidly proliferating cells.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In particular, it has been suggested that a small subpopulation of cells within tumors, called cancer stem cells (CSCs), by virtue of their relative resistance to chemotherapy may contribute to tumor recurrence (5,6). Consistent with these reports, several groups reported enrichment for CSCs when solid cancers were subjected to classical anticancer treatment (7)(8)(9)(10)(11). In accumulation, these studies suggest that significant improvement in patient outcome will require drugs that selectively target CSCs in combination with conventional chemotherapeutic regimens that target rapidly proliferating cells.…”
Section: Introductionmentioning
confidence: 84%
“…An explanation for this observation is partly provided by existing reports that NACT leads to enrichment of CSCs (7)(8)(9)(10)(11)39). However, this explanation alone is not enough to reason the recurrence of tumors as the CSC subpopulation, being a part of the primary tumor itself, must get removed during surgical resection of the tumor mass.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of mouse macrophages, PAI‐1 could induce the phosphorylation of focal adhesion kinase (FAK) to enhance the migration of macrophages . Treatment of FAK inhibitors or knockdown FAK expression by siRNA could reduce the self‐renewal capability and increase the radiosensitivity of ductal carcinoma in situ of breast cancer . The FAK expression in OSCC was significantly correlated with tumor size, neck node metastasis, and local recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…accurate quantitative assessment of their existence along with related biomarker expression in a tissue context will be essential to the design of therapeutic approaches that can deliver significant improvements in long term patient survival [2][3][4].…”
mentioning
confidence: 99%
“…Image analysis in this context can help go beneath the surface of tissue-based experiments, providing quantitative information on TICs that could help inform treatment decisions in a tumorspecific manner. Once target populations are identified, further image analysis studies of TICs can provide quantitative target engagement data, as shown in the case of FAK inhibition in breast cancer TICs [2]. Additionally, CNT helped improve the definition of TICs in renal cell carcinomas, where automated assessments of tumor cells demonstrated underestimation of TICs in RCC and highlighted shortcomings in limited dilution assays frequent used for the experiment identification of TIC populations [16].…”
mentioning
confidence: 99%